Paravertebral block vs. epidural block for percutaneous nephrolithotomy: A prospective, randomized study - Zhu, Pengcheng; Meng, Qianqian; Miao, YuanYuan; Zhou, Le; Wang, Chun; Yang, Haitao (Frontiers in Surgery, 2023)
Background Percutaneous nephrolithotripsy (PCNL) is the main method for urinary calculi. An anesthesia method with little effect on the blood circulation and which does not affect the postoperative activity of a patient is lacking. Objective To compare the effects of paravertebral nerve block (PNB) and epidural block (EPB) on quadriceps femoris muscle (QFM) strength in patients after PCNL. Methods 163 patients were separated into two groups: EPB (81) and PNB (82). Primary outcome parameters were QFM strength and range of motion (RoM) of the knee 1 h, 2 h, 3 h, and 24 h after anesthesia induction (AI). Secondary outcome parameters were: time from AI beginning to first ambulation; time of sensory-plane recovery; amount of additional analgesics given during and after surgery; prevalence of nausea and vomiting; duration of hospital stay (DoHS); mean arterial pressure (MAP), heart rate (HR), and oxygen saturation (SpO2) before, 0.5 h, and 1 h after AI; visual analog scale (VAS) score 0.5 h, 1 h, 2 h, 3h and 24h after AI. Results There was no significant difference in QFM strength or knee RoM before or 24 h after AI between the two groups (P > 0.05). The time from AI to first ambulation was shorter (P < 0.05) and the sensory plane took longer to recover (P < 0.05) in the PNB group than in the EPB group. The amount of additional analgesics during surgery was more in the PNB group than in the EPB group (P < 0.05), but there was no significant difference after surgery (P > 0.05). VAS scores were higher in the PNB group than in the EPB group 0.5 after AI (P < 0.05). MAP 1 h after AI was higher in the PNB group than in the EPB group (P < 0.05). There was no significant difference in the prevalence of postoperative nausea and vomiting, DoHS, HR, or SpO2 at 0.5 h and 1 h after AI between the two groups (P > 0.05). Conclusions For patients undergoing PCNL, PNB can meet the need for surgical analgesia while having little effect on QFM strength.